The prevalence and distribution of hypodontia inorthodontic patients in Bosnia and Herzegovina - Azra Jelešković; Indira Mujić Jahić; Aida Selmanagić; Sara Mujić; Lejla Redžepagić Vražalica (Journal of Health Sciences)
Introduction: The need for this study on the prevalence of hypodontia in a sample of orthodontic patients from Bosnia and Herzegovina arises from the fact that in the state of Bosnia and Herzegovina, there is a lack of data on the prevalence and distribution of hypodontia as a previously defined, growing global problem and that it could emphasize the importance of its early diagnosis, as this is still the best standard for preventing the occurrence of complications due to a lack of teeth. The aim of this retrospective study was to determine the prevalence and distribution of hypodontia in orthodontic patients in Bosnia and Herzegovina.